Exploring restoration options for habitats, species and ecosystem services in the European Union. Issue 4 (22nd April 2014) - Egoh, Benis N.; Paracchini, Maria L.; Zulian, Grazia; Schägner, Jan Philipp; Bidoglio, Giovanni; Jones, Julia
Summary The Convention on Biological Diversity (CBD) and the European Union have set a target of restoring 15% of degraded ecosystems by 2020 with the aim of conserving biodiversity and enhancing the supply of ecosystem services. This target must be implemented alongside other similar targets aimed at reducing the number of threatened habitat and species as assessed under the Birds and Habitats directives. However, there are several uncertainties associated with achieving these targets including the benefits of restoring biodiversity and ecosystem services, the contribution required from member states and the effect of different restoration scenarios on target achievement. In this study, we evaluate options that exist for meeting an EU‐wide 15% restoration target while conserving habitats and species and enhancing ecosystem services. We explored the effects of different restoration scenarios on the percentage of threatened habitat and species secured. Lastly, we explored the effects of including financial cost into the prioritization procedure. Focusing restoration efforts on habitats with inadequate conservation status in the reporting of the Habitats Directive provides the largest benefit for species and ecosystem services. If the restoration target is set at 10% for habitat and species with inadequate or most threatened conservation status, and at 2% for all ecosystem services, about 18% of EU ecosystems should be restored to meet these targets. When the target is set at 15% of habitat and species and 3% of all ecosystem services, results showed that France hosts the highest percentage of identified priority areas (13%) followed by Spain and Finland with about 11% and Sweden with 9%. However, these numbers change when financial cost is included alongside other criteria, with France containing 35% of all areas identified. Synthesis and applications. These results suggest that to achieve the greatest benefits, funding for restoration should be directed towards habitats with inadequate conservation status rather than to species. Countries with larger areas of threatened habitat and lower restoration costs may offer better opportunities to meet targets, but including cost at the EU level may result in unequal burden sharing among countries.